2021
DOI: 10.1002/anie.202106518
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Pd0‐ and PdII‐Catalyzed Cyclizations: Enantioselective Heck and Nucleopalladation Reactions

Abstract: An enantioselective consecutive cyclization/coupling process, catalyzed by palladium is reported. Stereoinduction arises from an enantioselective carbopalladation, generating an intermediate which promotes a nucleopalladation step. The dual cyclization sequence was compatible with a variety of alkyne‐tethered oxygen‐ and nitrogen‐centered nucleophiles, and a variety of alkenyl‐tethered aryl iodides, to forge numerous bisheterocycles in good yields and high regio‐ and enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 81 publications
0
29
1
Order By: Relevance
“…Dr. Alan Lough (University of Toronto) is thanked for X-ray crystallographic analysis. [29] We thank Dr. Darcy Burns and Dr. Jack Sheng (University of Toronto) for their assistance in NMR experiments.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Dr. Alan Lough (University of Toronto) is thanked for X-ray crystallographic analysis. [29] We thank Dr. Darcy Burns and Dr. Jack Sheng (University of Toronto) for their assistance in NMR experiments.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Nevertheless, improving the strategy further, the post coupling could be planned with a second cyclization at the coupling partner in order to produce multi-cyclic scaffolds. Representatives of such cascades 26 include the synthesis of bicycles accomplished by trapping an intramolecular Heck-coupling Pd intermediate with 2-alkynyl aniline as recently reported by Lautens 9 and Lin 10 et al and the synthesis of methylene-bridged benzofuranyl indolines achieved by trapping an oxindolyl-Pd intermediate with phenol derivatives as reported by Chen et al 11 Another impressive study was reported by Xu et al 12 for the synthesis of substituted indole scaffolds via dual cyclizative annulation of halo phenyl cyclobutanones with 2-alkynyl aniline. Recently, the Liu group 13 reported the synthesis of indolizine and indolizinone-derived bis-heterocycles through difunctionalization of acrylamide olefin and relay coupling of propargylic systems.…”
mentioning
confidence: 99%
“…1,2 Hence, numerous efforts have been made to produce these key scaffolds. 3 In light of the increasing focus on methylene-bridged bis-heterocyclic systems 9–11,25 for pharmaceutical applications, the linking of these two heterocycles would be expected to provide a gateway to a new class of molecules of therapeutic interest. To reduce the chemical waste, time and purification problems associated with constructing such systems in traditional linear pathways, 23 domino pathways from simpler and accessible starting materials are highly desirable to use.…”
mentioning
confidence: 99%
“…This reaction proceeds through an alkyl-Pd II intermediate which promotes a nucleopalladation of alkynetethered nucleophiles to generate doubly cyclized products. [9] To capitalize on this work, we envisioned utilizing a similar approach to generate biologically relevant olefinic-linked scaffolds. We hypothesized that alkyne tethered carbamoyl chlorides and aryl iodides can generate their corresponding vinyl-Pd II intermediates capable of promoting a similar cyclization to forge C(sp 2 )-C(sp 2 ) bonds (Scheme 1 c).…”
mentioning
confidence: 99%
“…We hypothesized that alkyne tethered carbamoyl chlorides and aryl iodides can generate their corresponding vinyl-Pd II intermediates capable of promoting a similar cyclization to forge C(sp 2 )-C(sp 2 ) bonds (Scheme 1 c). [9] Thus far, the reactivity of these vinyl-Pd II species has been harnessed in various transformations, [10][11][12][13][14][15] however more complex mechanistic manifolds to generate unsymmetrical linked heterocycles are yet to be studied. Our proposed strategy assembles tetrasubstituted olefins linking methylene oxindole and benzofuran scaffolds with their partnered heterocycle (Scheme 1 c).…”
mentioning
confidence: 99%